THE CONCEPT OF BUSINESS CLUSTERS AND ITS IMPACT ON TOURISM BUSINESS IMPROVEMENT - Mirčetić, Vuk; Vukotic, Svetlana; Cvijanović, Drago (Economics of Agriculture, 2019)
Increasing competition in the tourism market leads to the justified need for forming tourism clusters. Joining in clusters has numerous benefits for cluster members. Clustering leads to increased competitiveness of cluster members, because of the improved productivity and efficiency of work, adopted innovations, development of new technologies and introduction of the new quality standards and better market access. The purpose of this paper was to analyze tourism clusters models and to introduce the most suitable tourism cluster model for Serbia, based on the examples of good practice. Authors conducted a comprehensive literature review and proposed a new definition for cluster and accordingly determined new tourism cluster definition. Context of research is mostly related to cluster members. This paper contributes to research and development of clusters with a particular review of tourism clusters and suggests decision-makers in tourism what is the most suitable tourism cluster model they should consider.